(untitled) (REMUNOM, 2023)
Breastfeeding is the only food that should be offered to the child until six months of age. The process caused by swallowing breast milk develops and strengthens the bones of the face for speech, dentition development and chewing. Habits resulting from early weaning or replacement of breastfeeding by artificial breastfeeding and use of artificial nipples generates the occurrence of malocclusions, craniofacial changes, development of dentition and changes in the functions of the stomatognathic system. The objective of this study was, through a literature review, to point out, analyze and describe the predisposing factors and types of malocclusions found in children and to correlate the presence of malocclusions with the form of breastfeeding and children’s oral habits. The methodology used was the survey of studies in the databases Google Scholar, SciELO and PubMed. It is the responsibility of oral health professionals to keep up to date with regard to the development of malocclusions so that they can encourage and point out the benefits of breastfeeding for occlusal development, as well as point out the harms caused by deleterious habits.